Right‐hemispheric processing of non‐linguistic word features: Implications for mapping language recovery after stroke. Issue 6 (22nd February 2012) - Baumgaertner, Annette; Hartwigsen, Gesa; Roman Siebner, Hartwig
Abstract Verbal stimuli often induce right‐hemispheric activation in patients with aphasia after left‐hemispheric stroke. This right‐hemispheric activation is commonly attributed to functional reorganization within the language system. Yet previous evidence suggests that functional activation in right‐hemispheric homologues of classic left‐hemispheric language areas may partly be due to processing nonlinguistic perceptual features of verbal stimuli. We used functional MRI (fMRI) to clarify the role of the right hemisphere in the perception of nonlinguistic word features in healthy individuals. Participants made perceptual, semantic, or phonological decisions on the same set of auditorily and visually presented word stimuli. Perceptual decisions required judgements about stimulus‐inherent changes in font size (visual modality) or fundamental frequency contour (auditory modality). The semantic judgement required subjects to decide whether a stimulus is natural or man‐made; the phonologic decision required a decision on whether a stimulus contains two or three syllables. Compared to phonologic or semantic decision, nonlinguistic perceptual decisions resulted in a stronger right‐hemispheric activation. Specifically, the right inferior frontal gyrus (IFG), an area previously suggested to support language recovery after left‐hemispheric stroke, displayed modality‐independent activation during perceptual processing of word stimuli. Our findings indicate that activation of the right hemisphere during language tasks may, in some instances, be driven by a "nonlinguistic perceptual processing" mode that focuses on nonlinguistic word features. This raises the possibility that stronger activation of right inferior frontal areas during language tasks in aphasic patients with left‐hemispheric stroke may at least partially reflect increased attentional focus on nonlinguistic perceptual aspects of language. Hum Brain Mapp, 2013. © 2012 Wiley Periodicals, Inc.